Designing Services Using Quality Function Deployment - Ghobadian, Abby; Terry, A. J. (Marketing & Menedzsment, 2019)
The ability to design services that consistently improve the quality of service offered to customers is the key to any successful service quality improvement strategy. A major differentiating factor between service organisations is how well they identify customer requirements and deliver on those requirements. Quality Function Deployment (QFD), although traditionally associated with the design of physical products, is equally applicable to service design. QFD allows the development of a service design that focuses on the specific requirements of the customer. This paper examines the use of QFD by Alitalia in designing a new business class service. The authors present recommendations and a framework for the specific use of QFD by service organisations, that if utilised should secure competitive advantage.